2014
DOI: 10.1111/cfs.12139
|View full text |Cite
|
Sign up to set email alerts
|

Post‐adoption reunion sibling relationships: factors facilitating and hindering the development of sensitive relationships following reunion in adulthood

Abstract: A B S T R AC TThis paper explores findings from an exploratory study on sibling relationships following adoption reunion in adulthood. The qualitative data was gathered through in-depth interviews with 33 adopted adults who were reunited with their birth sibling(s) through an adoption agency in the Republic of Ireland. The findings throw light upon the development of the emotional, often complex, relationships which may emerge when siblings meet for the first time in adult life. Factors influential in facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
4
0
4
Order By: Relevance
“…En primer lugar, en cuanto a las características de los usuarios que demandan atención a los servicios posadopción, cabe destacar que las dos terceras partes son mujeres. Este dato también es compartido con otros países, donde las mujeres adoptadas tienden a demandar más ayuda o atención que los hombres, sobre todo en relación con la búsqueda de orígenes (Curtis & Pearson, 2010;O'Neill et al, 2016). Este dato no debería interpretarse, obligatoriamente, como que las mujeres estén encontrando mayores dificultades a lo largo de su vida.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…En primer lugar, en cuanto a las características de los usuarios que demandan atención a los servicios posadopción, cabe destacar que las dos terceras partes son mujeres. Este dato también es compartido con otros países, donde las mujeres adoptadas tienden a demandar más ayuda o atención que los hombres, sobre todo en relación con la búsqueda de orígenes (Curtis & Pearson, 2010;O'Neill et al, 2016). Este dato no debería interpretarse, obligatoriamente, como que las mujeres estén encontrando mayores dificultades a lo largo de su vida.…”
Section: Discussionunclassified
“…El contacto con sus hermanos biológicos puede ser una experiencia positiva y valiosa que contribuye a su crecimiento personal proporcionándole, en ocasiones, información sobre su familia biológica o compartiendo información acerca de ella, en caso de que ambos hermanos hayan sido adoptados (O'Neill et al, 2016). En los programas de formación para solicitantes de adopción se forma a los futuros padres en la necesidad de que, en caso de que los hermanos estén adoptados por distintas familias, se intente mantener el contacto entre ellos (León et al, 2010); igualmente, en la valoración de su idoneidad pueden mostrar su disposición al contacto con las familias que adopten a los hermanos de sus hijos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The importance of maintaining post-adoption contact between adopted children, particularly those placed at an older age, and their birth families is now increasingly accepted in social work practice in the West (O’Neill, McAuley and Loughran, 2016). In Western countries, open adoptions have encouraged the process of search and reunion, and post-adoption contact with birth relatives has been made either directly (face to face) or indirectly (‘letterbox contact’), typically mediated by an adoption agency.…”
Section: Challenges To the Digital Systemmentioning
confidence: 99%
“…Services most often requested by adoptive parents include concrete support and increased social support (Evan B. Donaldson Adoption Institute 2004). One study also found addressing marital stress of adoptive parents through participation in marriage enrichment events that successfully strengthened support networks, also reduced stress and increased feelings of competence in their parenting (O'Neill et al 2014).…”
Section: Navigating the Adoption Process Through The Child Welfare Systemmentioning
confidence: 99%